Evaluating the Law of Murder in Light of Soumya Judgment: A Medico- Legal Perspective (Indian Internet Journal of Forensic Medicine and Toxicology, 2018)
The decision of the Supreme Court in Govindaswamy murder case has sent shockwaves across the nation. Although some have lauded the judgment, other scholars have condemned it on account of misinterpretation of the law on the subject. This paper analyses the judgment on the basis of legal principles and forensic evidence. Murder, as laid down in the Penal Code 1860, is not restricted to an intention to cause death on the part of the accused; it also extends to cases where the intention is to cause injury sufficient to cause death. The degrees of intent conceived in the notion of murder vary as laid down in law and it if for the court to comprehend the same on the basis of evidences. Forensic science forms a significant part of the evidence needed to establish the nature of the injuries perpetrated and their probable impact on the victim. Such evidence, in turn, is reflective of the intent on the part of the accused. Unfortunately, the court overlooked the medical evidence in the instant case, thereby making way for the accused to escape liability for murder, in a gory incident that snuffed the life of a young energetic woman.
Keywords: Murder; Medical evidence; Intention; Injuries; Rape; Forensic science